Transient Thermal Deformation in a Thick Circular Plate with Internal Heat Source - Anjali K. Shinde, Kirtiwant P. Ghadle (International Journal of Advanced Science and Technology, 2020)
The present manuscript elaborates influence of internal heat generation on a thick circular plate by formulating direct, transient thermoelastic problem. A nonhomogeneous boundary value problem with radiation type of boundary conditions, which satisfies the time dependent heat conduction equation, and where the sources are generated within the circular plate according to the linear function of temperature is formulated and analysed. Finite Hankel, Marchi- Fasulo integral transforms and Goodier’s and Michell function are adopted to obtain the analytical solution. Outcomes are numerically verified by preparing a mathematical model for copper plate and results are depicted with the help of graphs.